Audit of prehospital thrombolysis by general practitioners in peripheral practices in Grampian. Issue 3 (1st September 1998) - Rawles, J; Sinclair, C; Jennings, K; Ritchie, L; Waugh, N
Abstract : Background: In the Grampian region early anistreplase trial (GREAT), domiciliary thrombolysis by general practitioners was associated with a halving of one year mortality compared with hospital administration. However, after completion of the trial and publication of the results, the use of this treatment by general practitioners declined sharply. Objective: To increase the proportion of eligible patients receiving timely thrombolytic treatment from their general practitioners. Setting: Practices in Grampian located ⩾ 30 minutes' travelling time from Aberdeen Royal Infirmary, where patients with suspected acute myocardial infarction were referred after being seen by general practitioners. Audit standard: A call-to-needle time of 90 minutes, as proposed by the British Heart Foundation (BHF). Methods: Findings of this audit of prehospital management of acute myocardial infarction were periodically fed back to the participating doctors, when practice case reviews were also conducted. Results: Of 414 administrations of thrombolytic treatment, 146 (35%) were given by general practitioners and 268 (65%) were deferred until after hospital admission. Median call-to-needle times were 45 (94% ⩽ 90) and 145 (7% ⩽ 90) minutes, respectively. Survival at one year was improved with prehospital compared with hospital thrombolysis (83% v 73%; p < 0.05). The proportion of patients receiving thrombolytic treatment from their general practitioners did not increase during the audit. Conclusions: In practices ⩾ 30 minutes from hospital, the BHF audit standard was readily achieved if general practitioners gave thrombolytic treatment, but not otherwise. Knowledge of the benefits of early thrombolysis, and feedback of audit results, did not lead to increased prehospital thrombolytic use. Additional incentives are required if general practitioners are to give thrombolytic treatment.